Socialization of Cayenne Pepper Plant Planting in the House Yard in Klambir Lima Village, Deli Serdang Regency - Desi Sri Pasca Sari Sembiring; Maimunah Siregar (Edujavare Publishing, 2023)
The yard of the house is one of the identities of a house. Yard land can be used for various purposes. In addition to beautifying the house, the yard can be used as a living pharmacy and nutrition garden. This service activity aims to educate and motivate the community to manage their yards effectively and efficiently, create a productive environment, and improve food security and the local economy. This method of service uses a Participatory Action Research (PAR) approach. This activity collaborates between the community and the service team of lecturers/students, where they must respect the leading role of the community. Lecturers/students and the community must work hand in hand in a participatory manner to make social change. The results of this service research show that the socialization of planting cayenne pepper plants in the yard can effectively improve community welfare and food security at the village level.